2022
DOI: 10.1155/2022/5714035
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Azadirachta indica as a Capping Agent for Antiviral Nanoparticles against SARS-CoV-2

Abstract: A rare type of pneumonia later on referred to as COVID-19 was reported in China in December 2019. Investigations revealed that this disease is caused by a coronavirus previously identified as SARS-CoV-2, and since then, it has become a global pandemic with new strains emerging rapidly as a result of genetic mutations. Various therapeutic options are being explored in order to eradicate this pandemic even though approved vaccine candidates are being currently rolled out globally. Most medicinal plant extracts h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…The 24,25 . As an outcome, it was concluded that these molecules could have a potential inhibitory effect on the 3 CL proenzyme, blocking the synthesis of 16 nonstructural proteins (nsp1-nsp16), which are necessary for replication of virus and thereby restricting viral survival in the host atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…The 24,25 . As an outcome, it was concluded that these molecules could have a potential inhibitory effect on the 3 CL proenzyme, blocking the synthesis of 16 nonstructural proteins (nsp1-nsp16), which are necessary for replication of virus and thereby restricting viral survival in the host atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…As described previously, the “Problem, intervention, comparison, outcome, and study type (PICOS)” procedure was used to formulate the study question [ 12 ]. We considered clinical and preclinical trial studies, clinical reviews, computational investigations, experimental studies, and epidemiological surveys, as well as hypothetical and theoretical studies.…”
Section: Methodsmentioning
confidence: 99%
“…Effectively high binding affinity have demonstrated for the COVID 3CL protease through molecular docking [ 74 ]. Nanoparticles derived from herbal sources like Azadirachta indica (neem plant) can be act as potential anti-SARS-COV-2 nanoformulation [ 75 ].…”
Section: Antiviral Nanotherapeutic Strategiesmentioning
confidence: 99%